Efficient and Air-Stable Planar Perovskite Solar Cells Formed on Graphene-Oxide-Modified PEDOT:PSS Hole Transport Layer - Luo, Hui; Lin, Xuanhuai; Hou, Xian; Pan, Likun; Huang, Sumei; Chen, Xiaohong (Nano-Micro Letters, 2017)
As a hole transport layer, PEDOT:PSS usually limits the stability and efficiency of perovskite solar cells (PSCs) due to its hygroscopic nature and inability to block electrons. Here, a graphene-oxide (GO)-modified PEDOT:PSS hole transport layer was fabricated by spin-coating a GO solution onto the PEDOT:PSS surface. PSCs fabricated on a GO-modified PEDOT:PSS layer exhibited a power conversion efficiency (PCE) of 15.34%, which is higher than 11.90% of PSCs with the PEDOT:PSS layer. Furthermore, the stability of the PSCs was significantly improved, with the PCE remaining at 83.5% of the initial PCE values after aging for 39 days in air. The hygroscopic PSS material at the PEDOT:PSS surface was partly removed during spin-coating with the GO solution, which improves the moisture resistance and decreases the contact barrier between the hole transport layer and perovskite layer. The scattered distribution of the GO at the PEDOT:PSS surface exhibits superior wettability, which helps to form a high-quality perovskite layer with better crystallinity and fewer pin holes. Furthermore, the hole extraction selectivity of the GO further inhibits the carrier recombination at the interface between the perovskite and PEDOT:PSS layers. Therefore, the cooperative interactions of these factors greatly improve the light absorption of the perovskite layer, the carrier transport and collection abilities of the PSCs, and especially the stability of the cells. Highlights: 1 PSCs (perovskite solar cells) with GO (graphene-oxide)-modified PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-polystyrenesulfonate) exhibit a higher efficiency and better stability. 2 GO-modified PEDOT:PSS surfaces exhibit superior wettability relative to PEDOT:PSS. 3 Hole extraction selectivity of GO inhibits carrier recombination of PSCs.